Towards MOOC and OER: the challenges ahead / Jowati Juhary and Mohd Sharil Salleh - Juhary, Jowati; Salleh, Mohd Sharil (UiTM Press, 2017)
The recently launched Malaysia Education Blueprint (Higher Education) has seen bold steps to improve and strengthen higher education quality in the country. Particularly challenging for the youngest public university, the National Defence University of Malaysia (NDUM) is embracing all 10 shifts outlined in the blueprint. This paper aims at examining the roles of and challenges faced by academics in adopting technology for teaching and learning. Looking at the scenario at the NDUM today, it appears that the academics are still uncertain about adopting the current learning management system (LMS) for aiding their teaching processes. The methodology used in this paper is mainly content analysis of existing policy documents. A brief survey was also conducted among academics and the data was used to support the arguments and findings from the content analysis. Initial findings suggest that the academics themselves, who attended the training on using the LMS, were not confident to teach other colleagues. What can be discerned from this is perhaps the level of readiness towards the use of technology in teaching and learning is still low. If this persists, Massive Open Online Course (MOOC) and Open Educational Resources (OER) may be a daunting objective to be achieved at the NDUM.